Nonverbal Communication Skill Practiced by Cardiologists at National Heart Institute, Malaysia - Govindaraju, Vimala (International Journal of Interdisciplinary Current Advanced Research (IJICAR), 2019)
Communication perceived as significant process that supports doctors convey the health care information to patients. The purpose of this research is to study nonverbal communication skills practiced by cardiologists to communicate with patients. Qualitative method thru phenomenological approach was applied to conduct in-depth interviews and observations with 8 cardiologists who participated as informants in the study at the National Heart Institute, Kuala Lumpur Malaysia. The data were transcribed verbatim and analyzed using ATLAS.ti 7 to code the key themes, sub-themes and inter-relationships. The research outcomes showed the nonverbal communication skills such as touch, body language and gesture, eye contact and tone of voice were essential elements used by the cardiologists during they consulting with their patients. The results suggested that doctors can be provided professional training to improve their nonverbal communication skills while consulting with patients. The nonverbal communication skill training can help the cardiologists effectively deliver health care service to their patients.